Implementasi Model Kooperatif Learning Tipe Think Pair Share (TPS) dalam Meningkatkan Pemahaman Materi Makanan Halalan Thayyiban pada Siswa Kelas XI MAN 2 Karawang - Aditya Ramadhan; Adiyas Adiyas; Alfia Aulia; Alya Safira; Dewi Nurhaliza (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
By implementing The cooperative learning method known as think, pair, share (TPS) paradigm in the eleventh grade at MAN Karawang, this study seeks to enhance students' comprehension of halal and healthy eating. The research has been conducted in two cycles using Classroom Action Research (CAR).methodology employed. There are twenty multiple-choice questions on the test that has been used. The findings of the study indicate that pupils' comprehension has improved. Just 15% of pupils finished the pre-cycle activities, with an average score of 66. This rose to 59% with a 73 average score in the initial cycle, and all students finished the activities with a mean score of 89 in the second. The pupils are encouraged to think critically, participate actively, and have discussions when Think Pair Share (TPS), a cooperative model, is applied. As a result, this strategy has been successful in improving students' comprehension through interaction